Evaluasi Kesuksesan Sistem TokSort Pada UMKM Devline Store Menggunakan Model DeLone dan McLean - Aditya Arya Respati; Erna Danianti; Aidina Ristyawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Manual order data management in small and medium enterprises may cause work delays, recording errors, and difficulties in monitoring order completion. This study evaluates the success of TokSort as a mobile-based information system for processing Comma Separated Values (CSV) order data at Devline Store using an adapted DeLone and McLean IS Success Model. A descriptive quantitative approach with an evaluative case study framing was applied. The respondents were 11 internal TokSort users directly involved in order data management, so total sampling was used. Data were collected through a Likert-scale questionnaire and observation, then analyzed using mean values, validity testing, reliability testing, and exploratory Spearman Rank correlation. The results show that all variables were classified as good: system quality 3.42, information quality 3.64, use 3.86, user satisfaction 3.59, and net benefits 3.73. Spearman Rank results indicate positive and significant relationships among the tested variables. These findings show that TokSort is considered successful in supporting order data processing, grouping, and monitoring based on internal users’ perceptions. However, system stability and the ability to reduce order processing errors still require improvement. This study contributes an empirical evaluation of an internal SME operational information system based on CSV file processing.